2021
DOI: 10.22438/jeb/42/4(si)/mrn-1542a
|View full text |Cite
|
Sign up to set email alerts
|

Host-specific influence on early growth and physiological attributes of sandal (Santalum album) grown in farmlands

Abstract: Aim: The present study aimed to investigate the host- specific compatibility of sandal (Santalum album) for better root proliferation and boosting the growth of tree. Methodology: Sandal (Santalum album) was grown with 8 different leguminous and non-leguminous species at early stage to evaluate its biometric growth (height and basal diameter) and physiological (chlorophyll, photosynthesis rate and transpiration rate) performance under field conditions. Results: Sandal grown with Sesbania grandiflora recorded… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…In the present comparative study on chlorophyll content of 7 different tree species, the maximum chlorophyll content was recorded in Neolamarckia cadamba with the value of 0.747 mg g -1 (Chlorophyll a), 0.454 mg g -1 (Chlorophyll b) and 1.201 mg g -1 (Total chlorophyll) followed by Melia dubia with total chlorophyll of 1.161 mg g -1 and Tectona grandis with the value of 1.111 mg g -1 (Table 3). The tree species with a maximum production of functional chloroplast perform photosynthesis action for food production, an important role in water development and physiological action (Pate, 2001;Bell and Adams, 2011;Cameron andSeel, 2007 andBalasubramanian et al, 2021). Neolamarckia cadamba, Melia dubia and Tectona grandis recorded the highest biometric observations, chlorophyll, photosynthesis rate and transpiration rate.…”
Section: Resultsmentioning
confidence: 99%
“…In the present comparative study on chlorophyll content of 7 different tree species, the maximum chlorophyll content was recorded in Neolamarckia cadamba with the value of 0.747 mg g -1 (Chlorophyll a), 0.454 mg g -1 (Chlorophyll b) and 1.201 mg g -1 (Total chlorophyll) followed by Melia dubia with total chlorophyll of 1.161 mg g -1 and Tectona grandis with the value of 1.111 mg g -1 (Table 3). The tree species with a maximum production of functional chloroplast perform photosynthesis action for food production, an important role in water development and physiological action (Pate, 2001;Bell and Adams, 2011;Cameron andSeel, 2007 andBalasubramanian et al, 2021). Neolamarckia cadamba, Melia dubia and Tectona grandis recorded the highest biometric observations, chlorophyll, photosynthesis rate and transpiration rate.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the non-significant (p ≥ 0.05) effect of host plant on both the photosynthetic rate and stomatal conductance of sandalwood suggests species ability to maintain both these processes equally, irrespective of types of host species. Moreover, despite influence of the hosts, sandalwood can adjust activities of chlorophyll, RuBPase, and stomata under the prevailing environmental conditions (Balasubramanian et al, 2021). Furthermore, Rocha et al (2014) showed that the lower content of nitrogen and chlorophyll and the altered RuBPase activities were responsible for decline in the photosynthetic rate of sandalwood.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have been conducted on different plant species to investigate the effects of salts on photosynthesis pigments and consistently reported that salt stress causes a decrease in photosynthetic rates at low salt concentrations and significant damage to chloroplast structures and photosynthetic machinery at high salt concentrations [ 33 , 34 , 35 , 36 ]. Particularly, enhanced chlorophyll and carotenoids in sandalwood with hosts M. dubia , D. sissoo , and A. indica under the control, as well as under different salinity levels (EC iw 3, EC iw 6, and 9 dS m −1 ), might be due to higher nitrogen supply from the host and higher chlorophyll synthase activity [ 37 ]. Simultaneously, the differential physiological response of sandalwood with distinct host species might be attributed to the host-induced regulations of light utilization efficiency, closure of stomata, and CO 2 levels in chloroplasts [ 38 , 39 ].…”
Section: Discussionmentioning
confidence: 99%